Laying the Foundation for Community-Driven, Open Cultural Gazetteers - El Khatib, Randa (KULA, 2019)
Geospatial humanities projects rely on information found in gazetteers to supply the infrastructure for projects. However, a majority of spatial gazetteers provide place names and geographical coordinates but lack contextualizing information that give meaning to a place, making them insufficient resources for humanities inquiry. In this article, I explore contemporary approaches to data collection and models for cultural gazetteers set forth by early modern chorographical traditions to lay the foundation for building community-driven, open cultural gazetteers. Concurrently, the role of the public in providing Volunteered Geographical Information (VGI) by harnessing user-friendly tools is explored.